EFEKTIVITAS METODE KISAH DALAM PEMBELAJARAN SEJARAH PERADABAN ISLAM - fahmi, faiz fikri; Hasim, Hasim; Firdiyani, Fitria; Haromaini, Ahmad (Universitas Islam Syekh-Yusuf, 2022)
The effectiveness of a learning method can be seen from the level of achievement of real goals with planned results. To achieve effectiveness in learning, a strategy or method is needed to make it easier for students to understand and understand learning. The learning model presented by the teacher has a very important role in realizing effective learning, so there is a need for a story method that is able to describe in detail in increasing the absorption of students and informing moral messages full of religious values ​​that are instilled by teachers in learning history. History is the study of events that have occurred in the past. This study concluded that the application of the story method in learning the history of Islamic Civilization can be effective and enjoyable because it is able to arouse student motivation, is more interesting and not boring. So that the subject matter of the history of Islamic Civilization is understood more quickly by students, and it is easier to remember material about the History of Islamic Civilization. Keywords: Effectiveness, Learning, Story Method, History Of Islamic Civilization.